(untitled) (Academicia Globe: Inderscience Research, 2022)
The article deals with problematic issues related to the peculiarities of the mechanism for the application of early preventive measures among the youth of Uzbekistan. The activities of law enforcement agencies that carry out a targeted, regular and comprehensive preventive function in this direction are analyzed. Attention is focused on the activities of the internal affairs bodies that implement general, special and individual prevention of offenses and crimes among young people in the early stages. Attention is drawn to ensuring and protecting the rights and legitimate interests of young people in the performance of their official duties by employees.